Single-particle elemental analysis of vacuum bag dust samples collected from the International Space Station by SEM/EDX and sp-ICP-ToF-MS. Issue 5 (25th March 2021) - Jahn, Leif G.; Bland, Garret D.; Monroe, Luke W.; Sullivan, Ryan C.; Meyer, Marit E.
Abstract: Air quality on board the International Space Station (ISS) is a significant concern for the long-term health of astronauts living on the station. Aerosolized particles are generated from a variety of sources, such as on-board equipment, electronics, and the astronauts themselves. Airborne particles can remain suspended for significant amounts of time due to the absence of gravitational settling. In this work, we examine the particulate matter on board the ISS through scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM/EDX) and single-particle multi-element inductively coupled plasma time-of-flight mass spectrometry (sp-ICP) analysis of two vacuum bag dust samples collected with a handheld vacuum cleaner used to clean surfaces and filter faces inside the ISS. SEM/EDX analysis shows that many large particles were collected. These particles are most commonly clothing fibers or of biological origin, along with smaller numbers of carbonaceous particles that may be from polymer and halopolymer materials. sp-ICP analysis quantitatively determined metal concentrations in particles approximately <10 µm in diameter and was able to identify several distinct particle compositions. Some of these, such as stainless steel (Fe-Cr-Ni-Mn), antiperspirant (Al-Zr), silver (Ag), and titanium oxide (Ti) particles, are consistent with particle types identified through past aerosol and vacuum bag sampling and analyses. Other types, including Fe-Al and other types of Al and Zr particles, do not have a clear origin consistent with past work. SEM/EDX and sp-ICP provide different but complementary information regarding the composition of particles obtained from vacuum bag dust samples. The material analyzed was obtained through the Divert Unwanted Space Trash (DUST) experiment on ISS, which returned vacuum bags to Earth for the purpose of understanding airborne particles in the unique ISS environment. Copyright © 2021 American Association for Aerosol Research